Maternal Thyroid Function during the Second Half of Pregnancy and Child Neurodevelopment at 6, 12, 24, and 60 Months of Age. (24th October 2011) - Chevrier, Jonathan; Harley, Kim G.; Kogut, Katherine; Holland, Nina; Johnson, Caroline; Eskenazi, Brenda
Abstract : Although evidence suggests that maternal hypothyroidism and mild hypothyroxinemia during the first half of pregnancy alters fetal neurodevelopment among euthyroid offspring, little data are available from later in gestation. In this study, we measured free T4 using direct equilibrium dialysis, as well as total T4 and TSH in 287 pregnant women at 27 weeks' gestation. We also assessed cognition, memory, language, motor functioning, and behavior in their children at 6, 12, 24, and 60 months of age. Increasing maternal TSH was related to better performance on tests of cognition and language at 12 months but not at later ages. At 60 months, there was inconsistent evidence that higher TSH was related to improved attention. We found no convincing evidence that maternal TH during the second half of pregnancy was related to impaired child neurodevelopment.